DIPLOMASI EKONOMI INDONESIA: TANTANGAN DARI UNDANG-UNDANG PENGURANGAN INSENTIF AS DAN DOMINASI NIKEL OLEH CHINA - Jhon Pattinussa; Qanszelir G. B. Pandjaitan XIV; Gusti Patading; Roy Vincentius Pratikno (Verity: Jurnal Ilmiah Hubungan Internasional (International Relations Journal), 2025)
Indonesia, as the world’s largest producer of nickel, faces significant challenges in leveraging its resources for economic development. These challenges are compounded by external pressures, including the U.S. Inflation Reduction Act (IRA), and internal issues related to China’s dominance in Indonesia’s nickel sector. Despite its vast nickel reserves, Indonesia is excluded from the green incentives provided under the IRA, which threatens to undermine its strategic position in the global nickel supply chain. The study seeks to understand the underlying factors driving this exclusion and the impacts of China’s dominance on Indonesia’s nickel industry. This research employs an explanatory qualitative approach, drawing from literature reviews and interviews with an industry expert. The methodology focuses on interpreting the interrelations between international trade policies, environmental sustainability, and Indonesia’s domestic challenges. The study identifies three key factors behind Indonesia’s exclusion from the IRA: the lack of a Free Trade Agreement (FTA) with the United States, environmental concerns over Indonesia’s mining practices, and the significant presence of Chinese companies in Indonesia’s nickel sector. China’s dominance has also led to environmental degradation, reduced domestic industrial competitiveness, and economic dependency. To address these challenges, the research proposes that Indonesia negotiate an FTA with the United States. Such an agreement would create a framework for accessing IRA incentives, strengthen Indonesia’s economic sovereignty, and mitigate China’s dominance. While the negotiation process will require strong political will and careful diplomacy, it presents a viable path for Indonesia to secure its economic and geopolitical interests.